The interaction of physical activity and sleep quality with depression and anxiety in older adults - Yuan, Yuqing; Huang, Wenying; Hu, Chang; Zhang, Wen (Frontiers in Public Health, 2025)
BackgroundWith the increase in the global aging population, the mental health of older adults has become increasingly prominent. This study aims to explore the relationship between the interaction of physical activity and sleep quality in older adults and depression and anxiety.MethodsA multi-stage stratified random sampling method was employed to survey various communities within Nanchang City, collecting data from 2,497 older adults. The assessment tools included the Physical Activity Rating Scale (PARS-3), Pittsburgh Sleep Quality Index (PSQI), the 9-item Patient Health Questionnaire (PHQ-9), and the 7-item Generalized Anxiety Disorder scale (GAD-7).ResultsAmong 2,497 participants, 582 (23.30%) had depressive tendencies; 1,122 (44.90%) had anxiety tendencies. The detection rate of depression and anxiety was higher in females than in males. Logistic regression analysis results showed that low physical activity was positively correlated with depression and anxiety (OR = 9.46; 3.66), while poor sleep quality was positively associated with depression and anxiety (OR = 2.40; 9.96) (P < 0.05). There is an interactive effect between physical activity and sleep quality in relation to anxiety and depressive symptoms in older adults. Specifically, compared to low physical activity combined with poor sleep quality, the combination of high physical activity and good sleep quality is associated with reduced levels of both anxiety and depression (P < 0.05).ConclusionThis investigation underscores the dynamic interplay among physical activity, sleep quality, depressive symptoms, and anxiety in older adults, forming a critical foundation for designing tailored interventions to enhance mental health outcomes in this population.